2017
DOI: 10.1002/evl3.2
|View full text |Cite
|
Sign up to set email alerts
|

Sperm storage by males causes changes in sperm phenotype and influences the reproductive fitness of males and their sons

Abstract: Recent studies suggest that environmentally induced effects on sperm phenotype can influence offspring phenotype beyond the classic Mendelian inheritance mechanism. However, establishing whether such effects are conveyed purely through ejaculates, independently of maternal environmental effects, remains a significant challenge. Here, we assess whether environmentally induced effects on sperm phenotype affects male reproductive success and offspring fitness. We experimentally manipulated the duration of sperm s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
66
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 54 publications
(144 reference statements)
2
66
2
Order By: Relevance
“…Post-meiotic sperm senescence is also apparent as a reduction in sperm motility and velocity (Gasparini, Kelley, & Evans, 2014;Gasparini, Daymond, & Evans, 2018;Pizzari et al, 2008;Vishwanath & Shannon, 1997; but see Firman, Young, Rowe, Duong, & Gasparini, 2015). Crucially, several recent innovative studies have shown that sperm competitiveness declines with sperm age (Gasparini et al, 2018;Gasparini, Dosselli, & Evans, 2017). These studies suggest that sperm age must be controlled for in age-based studies of male sperm traits.…”
mentioning
confidence: 99%
“…Post-meiotic sperm senescence is also apparent as a reduction in sperm motility and velocity (Gasparini, Kelley, & Evans, 2014;Gasparini, Daymond, & Evans, 2018;Pizzari et al, 2008;Vishwanath & Shannon, 1997; but see Firman, Young, Rowe, Duong, & Gasparini, 2015). Crucially, several recent innovative studies have shown that sperm competitiveness declines with sperm age (Gasparini et al, 2018;Gasparini, Dosselli, & Evans, 2017). These studies suggest that sperm age must be controlled for in age-based studies of male sperm traits.…”
mentioning
confidence: 99%
“…Younger males produced faster sperm than older males, while sperm age had the opposite effect: fresh sperm swam more slowly than stored sperm. This last result is particularly interesting because it contrasts with findings in guppies (Gasparini et al, 2014(Gasparini et al, , 2017(Gasparini et al, , 2019)-which, like mosquitofish, are poeciliids. Why aged sperm show increased speed in mosquitofish while showing reduced speed | 1189…”
mentioning
confidence: 67%
“…Sperm age may even affect the offspring's own gamete function: male guppies developing from eggs fertilized by old sperm go on to produce sperm that swim more slowly (Gasparini et al, 2017).…”
mentioning
confidence: 99%
“…Our very first paper, by Amanda Gibson et al (2017), is an empirical study examining one of the classical questions in evolutionary biology-the twofold cost of sex. Another paper considers how postcopulatory sexual selection has resulted in transgenerational fitness consequences of sperm storage in an internally fertilizing fish species (Gasparini et al 2017). Our first macroevolutionary paper (Greenberg and Mooers 2017) uses a comparative approach to show that speciation and extinction rates are correlated in amphibians; a pattern that has not been widely described in other taxonomic groups.…”
Section: Our First Articlesmentioning
confidence: 99%